Prevalence and Pattern of Diabetic Ketoacidosis among Children an Enugu, Southeast Nigeria: a 10 Year Retrospective Study - Ikenna Kingsley Ndu; Ugo Nnenna Chikani; Benedict Onyeka Edelu; Obinna Chukwuebuka Nduagubam; Adaobi Ijeoma Bisi-Onyemaechi; Uchenna Ekwochi; Isaac Nwabueze Asinobi (Baiman Bauntung Batuah Center, 2021)
Diabetic ketoacidosis (DKA) is the most severe complication in pediatric cases of type 1 diabetes and also the leading cause of death in these children. There is a broad geographic variation in the frequency of DKA at the onset of diabetes. This study sought to determine DKA's prevalence and pattern in Enugu and review the treatment and outcome over ten years. This retrospective study conduct in the Children Emergency Rooms (CHER) of the two tertiary institutions in Enugu State, southeast Nigeria: Enugu State University Teaching Hospital (ESUTH) and the University of Nigeria Teaching Hospital (UNTH). The biochemical criteria for the diagnosis of diabetic ketoacidosis (DKA) base on the presence of hyperglycemia (blood glucose > 11 mmol/L), acidosis (serum bicarbonate < 15 mmol/L), and ketonuria (urine ketone ?1+). A total of 16,488 children were admitted during the ten years, of which 21 children presented with DKA, representing a prevalence of 0.13%. Six (28.6%) of the patients were newly diagnosed diabetics, while fifteen (71.4%) known diabetics, of which 9 (60%) were presenting with DKA for the first time. A total of two patients died, giving a mortality rate of 9.5%. The rest treated and discharged. The total hospitalization duration ranged from 1–31 days, with a mean duration of 13.3 ± 7.5 days. This study has revealed some of the challenges with the management of children with DKA and the unacceptably high mortality rate.